2002
DOI: 10.1002/ijc.10395
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of interleukin‐15 in vivo enhances antitumor activity against mhc class I‐negative and ‐positive malignant melanoma through augmented NK activity and cytotoxic T‐cell response

Abstract: Key words: tumor immunity; IL-15; CTL; NK cells; transgenic miceInterleukin (IL)-15 is a 15 kDa cytokine 1,2 that uses ␤ and ␥ chains of the IL-2 receptor for signal transduction and shares many of the biologic activities of IL-2, including the induction of proliferation of phytohemagglutinin-stimulated normal PBMCs, NK cells and B cells and the generation of CTLs and lymphokineactivated killer (LAK) cells in PBMCs in vitro. [1][2][3][4][5][6][7] Memory phenotype CD8 ϩ T cells have also been shown to respond p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 40 publications
1
37
1
2
Order By: Relevance
“…[30][31][32] It is widely accepted that MHC class I-negative tumor cells are susceptible to NK cells, while MHC class I-positive tumor cells are resistant to NK cells. 21,24,29 The results of the present study, however, showed that in vivo treatment with antiasialoGM1 Ab also abrogated the antitumor activity in AC-1-treated mice inoculated with MHC class I-positive B16 K b cells. Although B16 K b melanoma cells express MHC class I molecules on their surfaces, the level of MHC class I expression of the tumor was shown to be significantly lower than those of tissue cells (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…[30][31][32] It is widely accepted that MHC class I-negative tumor cells are susceptible to NK cells, while MHC class I-positive tumor cells are resistant to NK cells. 21,24,29 The results of the present study, however, showed that in vivo treatment with antiasialoGM1 Ab also abrogated the antitumor activity in AC-1-treated mice inoculated with MHC class I-positive B16 K b cells. Although B16 K b melanoma cells express MHC class I molecules on their surfaces, the level of MHC class I expression of the tumor was shown to be significantly lower than those of tissue cells (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…IL-15 has also been implicated in the augmentation of NK cell cytotoxicity and IFN-␥ secretion (9,11). Additionally, IL-15-transgenic mice have been found to be more resistant to tumors (21). The effects of IL-15 on the development, homeostasis, survival, and activation of NKDC are unknown.…”
Section: Nk Dendritic Cells Expanded In Il-15 Exhibit Antitumormentioning
confidence: 99%
“…The antitumor potential of IL-15 was observed in mouse models employing recombinant IL-15 (16,17), antibody-IL-15 fusion protein (18), IL-15 gene-modified tumor cells (19,20), and IL-15 transgenic mice (21). The relevance of IL-15 trans-presentation for an efficient antitumor response was shown in a mouse model with IL-15Ra-transfected MC38 tumor cells.…”
Section: Introductionmentioning
confidence: 99%